293 Treatment strategies and survival of women with malignant ovarian germ cell tumours – an analysis of the ago-corsett database. (4th December 2020) - Hasenburg, Annette; Plett, Helmuth; Harter, Philipp; Kommoss, Stefan; Keul, Jaqueline; Roser, Eva; Czogalla, Bastian; Bossart, Michaela; Link, Theresa; Klar, Maximilian
Abstract : Introduction/Background: Malignant ovarian germ cell tumours (OGCT) account for about five percent of all ovarian malignancies in Western countries. The Arbeitsgemeinschaft fuer Gynaekologische Onkologie (AGO) has established a clinicopathological (Current Ovarian geRm cell and SEx cord stromal Tumour Treatment strategies, CORSETT) database for a better documentation and understanding of this rare disease. Here, we present the first descriptive analysis for patients with confirmed OGCT from the CORSETT database. Methodology: 20 German centres entered mixed retro- and prospective data of OGCT patients with histology specimens available treated between 2000 to 2014 into the CORSETT database. An independent CORSETT pathology reference panel checked the primary histological diagnosis. We conducted a descriptive analysis of the treatment strategies and created Kaplan-Meier curves and cox regression analyses for the survival analysis. Results: The reference pathology panel diagnosed 36 patients with dysgerminoma (FIGO stage I = 77.8%), 20 patients with mixed OGCT (FIGO stage I = 66.7%) and 21 with malignant teratoma (FIGO stage I = 85%). The median age of patients with dysgerminoma was 30.2 years (mixed OGCT: 35.6 and teratoma 36.4 years). 23 of dysgerminoma (63.8%), six of mixed OGCT (31.6%) and eight of teratoma (38.1%) patients were treated with laparoscopy and the tumour ruptured intraoperatively in 21% (dysgerminoma, mixed OGCT: 50%, teratoma: 22%) of the cases. 29 dysgerminoma (85.6%), 15 mixed OGCT (78.9%) and 17 teratoma (85%) patients received fertility-sparing surgery. 20 of dysgerminoma (57%), 14 of mixed OGCT (70%) and 11 of teratoma (55%) patients received adjuvant chemotherapy which decreased the likelihood of disease recurrence significantly in mixed OGCT patients to the highest degree (hazard ratio = 0.21, 95% confidence interval 0.04 – 0.97). In total, two dysgerminoma (4.6%), nine mixed OGCT (45%) and three teratoma (14.3%) patients experienced disease recurrence. The median progression-free and overall survival was not reached in the total cohort of OGCT patients. Conclusion: In this analysis, OGCT patients had an excellent prognosis despite non-negligible rates of intraoperative tumour spillages. Adjuvant chemotherapy appeared to prevent disease recurrence. Disclosures: